Quantitative Assessment of the Bioburden of High-Touch Environmental Surfaces in Pediatric Operating Rooms. (4th October 2017) - Ackerman, Kathleen; Salsgiver, Elizabeth; Martin, Elena; Maykowski, Philip; Calfee, David P; Furuya, E Yoko; Saiman, Lisa
Abstract: Background: Previous studies have linked healthcare-associated infections to bacterial pathogens in the operating room (OR) environment. The purpose of this study was to determine the bioburden on OR surfaces to guide future quality improvement efforts and optimize OR cleanliness. Methods: This study was performed in the pediatric ORs of a 200-bed, academically affiliated, children's hospital with ~6000 general and subspecialty surgical procedures annually. Immediately after cases were finished, but prior to cleaning, the 3M Clean-Trace Clinical Hygiene Monitoring System was used to quantify bioburden (in surface ATP concentration) on 24 surfaces in each of 8 ORs. These 24 surfaces were previously identified by the Association of periOperative Registered Nurses as high-touch surfaces and various disciplines are responsible for their cleaning. Each OR was sampled 1–4 times. A surface passed the test of cleanliness if the result was <250 relative light units (RLUs). Results: In all, 364 surfaces were tested. The median RLUs were <250, 250–850, and >850 RLUs for 7, 11, and 6 surfaces, respectively. Of the 24 surfaces tested, all demonstrated bioburden ≥250 at least once. Median RLUs for each surface ranged from 39-2282 and median RLUs for each OR ranged from 196 to 1534. The highest bioburden occurred following cardiac surgery (median 1534, range 24-13275 RLU) and the lowest bioburden occurred after neurosurgery (median 196, range 23-2475 RLU). The surfaces with the highest bioburden were the anesthesia keyboards (median 2282, range 347-38376 RLU) and core door handles (median 1471, range 140–6788 RLU) and those with the lowest bioburden were the Mayo stand (median 39, range 19-765 RLU) and back table (median 39, range 17-406 RLU). Conclusion: ATP testing demonstrated that most OR surfaces were contaminated with organic material. While OR surfaces prior to cleaning are expected to be contaminated, these data highlight the importance of cleaning/disinfection. These findings are being used to develop educational tools and interventions for the interdisciplinary OR team, which will focus on delineation of cleaning responsibilities, the use of appropriate cleaning products, and audits of end-of-case cleaning and terminal cleaning. Disclosures: All authors: No reported disclosures.